Interspecific Mating Effects on Locomotor Activity Rhythms and Refractoriness of Aedes albopictus (Diptera: Culicidae) Females - Thais de Souza Feitoza; Victor Henrique Ferreira-de-Lima; Daniel Cardoso Portela Câmara; Nildimar Alves Honório; L. Philip Lounibos; Tamara Nunes Lima-Camara (Insects, 2020)
This study tests the hypotheses that the locomotor activity of Ae. albopictus females is not significantly altered by the presence of accessory gland (AG) extracts from conspecific and heterospecific males, and that Ae. albopictus females remain receptive to mating with conspecific males even after receiving AG of Ae. aegypti males. Virgin Ae. albopictus females were injected with saline (control group), AG extracts of Ae. aegypti males (aegMAG) or AG extracts of Ae. albopictus males (albMAG). Locomotor activity was evaluated under 12 h of light and 12 h of darkness at 25 °C. All live Ae. albopictus females were subsequently exposed to conspecific males for 48 h, and their spermathecae were dissected for the presence of sperm. Females injected with aegMAG and albMAG showed significant decreases in total, diurnal and diurnal without lights-on Period activities. Females injected with aegMAG showed significant decreases in nocturnal and nocturnal without lights-off period activities. Females injected with albMAG showed significant decreases in lights-off activity. A total of 83% of Ae. albopictus females injected with aegMAG and 10% of females injected with albMAG were inseminated by conspecific males. These results, coupled with our previous paper on MAG and interspecific mating effects on female Ae. aegypti, demonstrate contrasting outcomes on locomotor activities and loss of sexual receptivity, both conspecific and heterospecific MAGs capable of sterilizing virgin Ae. aegypti, but only conspecific MAGs sterilizing Ae. albopictus, whereas locomotor activities were depressed in females of both species after heterospecific and conspecific injections or treatments.